2006
DOI: 10.1071/is05036
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of the new Australian wolf spider genus Tuberculosa (Araneae:Lycosidae)

Abstract: The new Australian wolf spider genus Tuberculosa is revised, with T. harveyi, sp. nov. from the Northern Territory as type species. The genus includes a further three species from northern Queensland: T. austini, sp. nov., T. hoggi (Framenau & Vink, 2001), comb. nov. and T. monteithi, sp. nov. The genus is defined by a unique sexual dimorphism: males carry modified tubercular setae on the ventral side of the third coxae, which are here compared to the knobbed setae that can be found on the ventral surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…its transverse orientation, with ventrally directed spur and a sinuous channel on its dorsal surface (Dondale, 1986). Knowledge of Australian Lycosinae is poor, although there have been several recent generic revisions, including Dingosa Roewer, 1955, Knoelle Framenau, 2006, Mainosa Framenau, 2006 and Tuberculosa Framenau & Yoo, 2006 and Venatrix Roewer, 1960 (Framenau & Vink, 2001; Framenau, 2006a, b; Framenau & Yoo, 2006; Framenau & Baehr, 2007). Molecular studies have suggested two distinct clades of Australian Lycosinae; one has an oriental origin ( Venatrix and Tuberculosa ) and the remaining genera represent a Gondwanan clade with the closest relative in the taxon sampled, Pavocosa gallopavo (Mello‐Leitão, 1941), from South America (see Murphy et al ., 2006; Gotch et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…its transverse orientation, with ventrally directed spur and a sinuous channel on its dorsal surface (Dondale, 1986). Knowledge of Australian Lycosinae is poor, although there have been several recent generic revisions, including Dingosa Roewer, 1955, Knoelle Framenau, 2006, Mainosa Framenau, 2006 and Tuberculosa Framenau & Yoo, 2006 and Venatrix Roewer, 1960 (Framenau & Vink, 2001; Framenau, 2006a, b; Framenau & Yoo, 2006; Framenau & Baehr, 2007). Molecular studies have suggested two distinct clades of Australian Lycosinae; one has an oriental origin ( Venatrix and Tuberculosa ) and the remaining genera represent a Gondwanan clade with the closest relative in the taxon sampled, Pavocosa gallopavo (Mello‐Leitão, 1941), from South America (see Murphy et al ., 2006; Gotch et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Framenau 2005;Framenau 2007), and Lycosinae (e.g. Framenau and Vink 2001;Framenau and Yoo 2006;Framenau and Baehr 2007). The Lycosinae includes the largest of the Australian wolf spiders, often living in permanent burrows, which has allowed them to colonise the arid centre with enormous success (Framenau and Baehr 2007;Langlands and Framenau 2010).…”
Section: Lycosidaementioning
confidence: 99%
“…Costacosa differs from Hogna by the shape of the male and female genitalia as Hogna have a very simple, triangular tegular apophysis in the male pedipalp and a simple, inverted T-shaped median septum of the female epigyne Fuhn and Niculescu-Burlacu 1971). Costacosa differs from Venatrix and Tuberculosa by the lack of an apical cymbial hook in males (Framenau and Vink 2001;Framenau and Yoo 2006).…”
Section: Diagnosismentioning
confidence: 99%
“…Australian genera of the Gondwanan lineage that were recently revised include Dingosa Roewer, 1955 andHoggicosa Roewer, 1960, and the monotypic Knoelle , Mainosa Framenau, 2006and Tapetosa Framenau et al 2009 (Framenau 2006a, b;Framenau and Baehr 2007;Framenau et al 2009;Langlands and Framenau 2010). The South-East Asian lineage is currently represented by Venatrix Roewer, 1960and Tuberculosa Framenau and Yoo, 2006(Framenau 2006dFramenau and Vink 2001;Framenau and Yoo 2006). Other largely Northern Hemisphere lycosine genera currently reported from Australia, such as Alopecosa Simon, 1885, Geolycosa Montgomery, 1904, Lycosa Latreille, 1804 and Trochosa C. L. Koch, 1847, represent historical taxonomic artefacts as early European arachnologists generally placed Australian species in taxa they were familiar with.…”
Section: Introductionmentioning
confidence: 99%